Raising Healthy Children: Shellfish Allergies - Kate Bennett; Karla P. Shelnutt; Gail P. A. Kauwell (EDIS)
Learning that your child has a shellfish allergy can be scary. But having a plan and knowing how to treat and avoid a reaction to shellfish can ease this fear and keep your child safe. This publication explains shellfish allergies and provides information on the symptoms and how to respond if a reaction occurs. There are also tips to make it easier to manage your child’s shellfish allergy at home and away from home.This 4-page fact sheet was written by Kate Bennett, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, November 2013. http://edis.ifas.ufl.edu/fy1402